2021
DOI: 10.1186/s12864-020-07361-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of gene expression profiles in differentiated subcutaneous adipocytes between Jiaxing Black and Large White pigs

Abstract: Background Chinese domestic pig breeds are reputed for pork quality, but their low ratio of lean-to-fat carcass weight decreases production efficiency. A better understanding of the genetic regulation network of subcutaneous fat tissue is necessary for the rational selection of Chinese domestic pig breeds. In the present study, subcutaneous adipocytes were isolated from Jiaxing Black pigs a Chinese indigenous pig breed with redundant subcutaneous fat deposition and Large White pigs a lean-type … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…GO annotation result showed that GRM4 was involved in activation of MAPK activity (Table S 4 ). The MAPK pathway was demonstrated in numerous studies to be crucial for adipogenesis [ 54 , 55 ]. So GRM4 might play an important role in adipogenesis by activation of MAPK activity.…”
Section: Discussionmentioning
confidence: 99%
“…GO annotation result showed that GRM4 was involved in activation of MAPK activity (Table S 4 ). The MAPK pathway was demonstrated in numerous studies to be crucial for adipogenesis [ 54 , 55 ]. So GRM4 might play an important role in adipogenesis by activation of MAPK activity.…”
Section: Discussionmentioning
confidence: 99%
“…The Ras-MAPK signaling pathway can control cell proliferation, differentiation, and survival through the kinase cascade [ 72 , 73 , 74 ]. Many studies have shown that Ras-MAPK signaling pathway is crucial for adipogenesis [ 75 , 76 ]. Therefore, it could be inferred that BRAP gene might regulate fat deposition in pigs through Ras-MAPK signal pathway, thereby affecting average daily gain of pigs.…”
Section: Discussionmentioning
confidence: 99%
“…FOS is an inflammatory and apoptosis-related gene [20][21], and in recent years, studies have reported that FOS may be related to pig muscle growth weight [22]. Studies have also shown that EGR1 is an early growth response protein, which has an important relationship with cell proliferation, differentiation and apoptosis, Egr1 expression is activated by a variety of MAPK-inducing factors [23][24][25], Multiple studies have shown that the MAPK pathway regulates the expression of adipogenesis transcription factors during adipogenesis [26][27]. EGR1 knockout in mice can reduce leptin expression in basal cells [28].…”
Section: Discussmentioning
confidence: 99%